ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH UANG YANG BEREDAR 1990-2019 - Muhammad Subhan Iswandi; Umaruddin Usman (Jurnal Ekonomi Regional Unimal, 2022)
This study aims to analyze the analysis of factors that influence the amount of money  in  circulation from  1990  to  2019.  The  data  used  in  this  study  is secondary data for the period 1990 - 2019. This research model uses the Vector Autoregression (VAR) model. The unit root test was carried out with the Augmented Dickey Fuller (ADF) test where all the stationary variables were second different. The results of the study are based on VAR analysis. Foreign debt affects the money supply in Indonesia. Non-oil exports affect the money supply in Indonesia. Non-oil and gas imports affect the money supply in Indonesia. The current account balance has no effect on the money supply in Indonesia and inflation has no effect on the money supply in Indonesia.